First Molecular Detection of Piroplasm Infection in Pet Dogs from Gansu, China - Niu, Qingli; Yang, Jifei; Liu, Zhijie; Gao, Shandian; Pan, Yuping; Guan, Guiquan; Chu, Yuefeng; Liu, Guangyuan; Luo, Jianxun; Yin, Hong (Frontiers in Microbiology, 2017)
Babesiosis, the hemolytic disease caused by Babesia, which is a tick-transmitted obligate intraerythrocytic protozoan parasite. This disease is responsible for significant mortality and morbidity rates and enormous economic losses to the livestock industry in tropical and subtropical regions worldwide. In this study, blood samples were collected from 141 pet dogs from Gansu, China, and analyzed for Babesia or Theileria spp. infection using specific PCR and sequencing based on 18S rRNA gene fragments. The results indicated that 18S rRNA gene sequences from 11 samples were similar to the 18S rRNA gene sequences in Babesia canis vogeli (2) and Theileria sinensis (9). The total infected rates of B. canis vogeli and T. sinensis were 1.4% (2/141) and 6.4% (9/141), respectively. This represents the first molecular report of T. sinensis in dogs worldwide and of B. canis vogeli in dogs from Gansu province of China. Furthermore, the finding of T. sinensis in dogs may represent the common infection of this parasite occurring in Gansu.